BOOSTING STUDENTS’ READING COMPREHENSION ATTAINMENT WITH FLIPPED CLASSROOM MODEL: A PILOT STUDY AT STATE POLYTECHNIC OF SRIWIJAYA - Ardiansyah, Welly; Meirani, Wasitoh; Risnawati (International Online Journal of Education and Teaching, 2022)
The study investigated the impact of the flipped classroom on the second semester students in accounting class. Participants (n=50) were assigned to a control group (using traditional instruction) or an experimental group (using flipped classroom model). A quasi-experiment in reading comprehension course on the second semester in academic year 2021-2022 was used. The Kolmogorov-Smirnov and Shapiro-Wilk test were .083 and .156 for pre-test control group, .200 and .787 for post-test control group, .119 and .185 for pre-test experimental group, and .095 and .101 for post-test experimental group suggesting normal distributions (p>.05). Homogeneity tests based on mean, median, median and with adjusted df, and trimmed mean were .857, .827, .827, and .857 indicating that Homogeneity tests were >.05. Pre-test scores of both groups compared by using independent t-test revealed no significant difference between these groups (.505>.05), while post-test scores of both groups showed significant difference (.000<.05). ANCOVA was conducted to see an interaction between the treatment and the post-test scores in which F=38.642, p<.05 means that the experimental group outperformed the control group. Likert Scale Questionnaire revealed that the students were highly satisfied with the flipped classroom. This also confirmed the difference between the control and experimental groups.